QR Code Generator: Studi Kasus Orisinalitas Produk Kasepuhan Sinar Resmi - Tarikh Agustia Ijudin; Adhitia Erfina (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Kasepuhan Sinar Resmi in Cisolok District is an inseparable part of the Ciletuh Geopark Area. The village has several original products made directly by the local community, and marketed online. However, it is often used as a crime by some people who fake products made by the Kasepuhan Sinar Resmi community for personal gain. This crime is certainly very detrimental to the people of Kasepuhan Sinar Official, they do not get the slightest profit from the goods sold and the safety of the product is doubted. The purpose of this study is to create a system that guarantees the authenticity of the sold's products by the Kasepuhan Sinar Resmi community, so that sellers and buyers can get the benefit. In this study, the system development method used is an Object Oriented Programming (OOP) approach with tools such as Use Case Diagrams, Activity Diagram. From the existing problems, this research focuses on the design and construction of a QR Code Generator to detect the originality of the Kasepuhan Sinar Resmi’s product, this is conducted so that people get the original Kasepuhan Sinar Resmi’s product.